Pengaruh Capital Intensity, Inventory Intensity, Advertising Intensity, dan Sales Growth terhadap Tax Avoidance - Intan Larisa Aurellia; Dika Puspitaningrum (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The primary goal of this research is to measure the impact of Capital Intensity (CI), Inventory Intensity (II), Advertising Intensity (AI), and Sales Growth (SG) on corporate Tax Avoidance (TA). The study relies on secondary data analyzed through a quantitative approach, focusing on the numerical evaluation of available data. The sample comprises 19 retail sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Using purposive sampling with a three-year observation period, the research obtained 57 valid panel data observations that provide a solid basis for statistical analysis. Two main analytical stages were used: descriptive statistics to understand the data and multiple linear regression to test the hypotheses. The results show that: (1) CI significantly influences TA, (2) II significantly influences TA, (3) AI has no significant impact on TA, and (4) SG shows no significant effect on TA. However, an overall test confirms that the combined effect of Capital Intensity, Inventory Intensity, Advertising Intensity, and Sales Growth significantly influences Tax Avoidance, emphasizing the importance of comprehensive considerations in tax management practices within the retail sector sector.